2021
DOI: 10.3390/rs13101869
|View full text |Cite
|
Sign up to set email alerts
|

Can Commercial Low-Cost Drones and Open-Source GIS Technologies Be Suitable for Semi-Automatic Weed Mapping for Smart Farming? A Case Study in NE Italy

Abstract: Weed management is a crucial issue in agriculture, resulting in environmental in-field and off-field impacts. Within Agriculture 4.0, adoption of UASs combined with spatially explicit approaches may drastically reduce doses of herbicides, increasing sustainability in weed management. However, Agriculture 4.0 technologies are barely adopted in small-medium size farms. Recently, small and low-cost UASs, together with open-source software packages, may represent a low-cost spatially explicit system to map weed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…Results showed good performances of detecting weed by testing ANN, OBIA, and MLL (Figure 2). Moreover, this study also showed the feasibility of adopting a completely open-source workflow for RGB image processing (OpenDroneMap software) and automatic weed extraction by using open algorithms and packages available in SAGA and QGIS software (Mattivi et al, 2021).…”
Section: Vegetation Monitoringmentioning
confidence: 80%
See 2 more Smart Citations
“…Results showed good performances of detecting weed by testing ANN, OBIA, and MLL (Figure 2). Moreover, this study also showed the feasibility of adopting a completely open-source workflow for RGB image processing (OpenDroneMap software) and automatic weed extraction by using open algorithms and packages available in SAGA and QGIS software (Mattivi et al, 2021).…”
Section: Vegetation Monitoringmentioning
confidence: 80%
“…One promising application of automatic mapping specific plant species in organic farming and in agroecology is the use of low-cost commercial drones, equipped with a standard RGB camera. A representative case study in the framework of organic farming is reported by Mattivi et al (2021). In this experimental research, a Parrot Anafi UAV was adopted to automatically extract presence of Sorghum halepense, Chenopodium and Amaranthus retroflexus in a maize-crop field.…”
Section: Vegetation Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…GPS is widely used for weed control in precision agriculture, for example, so mechanical weed control can replace chemical control (Partel et al, 2019). Recently, some studies have used GPS instead of optical sensors (Mattivi et al, 2021). GIS is invaluable in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Mattivi et al[54] Wheat Optimized a deep residual convolutional neural network (CNN) (ResNet-18) for classifying weed and crop plants in UAV imagery.…”
mentioning
confidence: 99%